(untitled) (Research, Society and Development, 2020)
Brazilian breeding programs usually aim at finding genotypes with early cycle and high grain yield. Thus, this study aimed to select early soybean lines with high grain yield for the Cerrado region. The experiment was carried out in the 2017-2018 season, in the Universidade Federal de Mato Grosso do Sul, Campus Chapadão do Sul, and consisted of an augmented blocks design, using 196 lines and ten controls, with five replications for each control. The experiment evaluated the traits plant height, number of days to flowering, and grain yield. After verifying the genetic variability for all traits, two selection methods were evaluated, the direct selection in each trait and the simultaneous selection (to decrease plant height and number of days to flowering and increase grain yield, using the Mulamba and Mock index). The latter considered two scenarios were when establishing the economic weight: the coefficient of genotypic variation (CVg) and arbitrary weights. Direct selection on the variables had unsatisfactory results. The Mulamba and Mock revealed unsatisfactory results when using CVg as the economic weight and satisfactory results when using arbitrary weights.